Clinical Decision-Making During Psychiatric Ward Rounds - Holzhüter, Fabian; Schuster, Florian; Heres, Stephan; Hamann, Johannes (Frontiers in Psychiatry, 2021)
Introduction: For psychiatric in-patients, ward rounds are a prominent occasion for decision making. As previous findings on shared decision-making (SDM) patterns mostly derive from out-patients and one-to-one-consultations, it was our aim to investigate SDM during psychiatric ward rounds. Methods: We conducted a cross-sectional study and included n=62 in-patients from seven different psychiatric wards. We collected data from the patient and the treating physician before and after ward rounds and recorded the interaction. Results: We identified two groups of patients regarding their attitude towards ward rounds (no expectations vs. clear agenda). The latter showed higher active engagement, expected more decisions to be made and discussed more topics. Generally, observer rated SDM was low, with vast differences between the doctors’ and the patients’ perception. Conclusion: Doctors and patients perceive ward rounds differently and there is a discrepancy between subjective and objective involvement. A rather paternalistic doctor-patient-relationship is observed, while patients feel sufficiently involved and vastly satisfied. The potential of ward rounds maximizes if patients have an agenda. Consequently, motivating patients to prepare themselves towards ward rounds should be part of the weekly routine, as well as improving patient participation and information procedures during ward rounds.